Financial constraint and cash flow sensitivity of Brazilian companies - Bragioni, Camila Aparecida; Lopes Santos, David Ferreira [UNESP] (Univ Icesi, 2018)
This study analyzes the impact of financial constraint on the cash sensitivity of Brazilian companies, based on an empirical model that extrapolates literature with the moderation of the level of governance and the geographical vicinity of companies to the main financial center of the country. This issue is relevant in emerging markets due to poor market efficiency, economic inequality and access to financial market. A regression analysis performed with panel data in a sample of 319 companies (2009-2016) demonstrated a positive and significant impact of financial constraint on cash flow sensitivity, with specificities for the Brazilian market. Both theoretical and practical contributions are proposed, particularly around the need for internalization of the Brazilian stock exchange market.
Keywords: information asymmetry; emerging economies; indebtedness; investment; geographic location